Photocatalytic Degradation of Methylene Blue Dye using PANI‐CuFe2O4 Nano Composite - Tisa Rani Saha; Md. Ahsan Habib; S. M. Imran Ali; Jannatul Naime; Md. Mahiuddin; Shaheen M. Sarkar; Md. Abu Rayhan Khan; Kaykobad Md Rezaul Karim (Global Challenges)
Abstract The present perspective accentuates the synthesis of PANI‐CuFe2O4 (PCF) nanocomposite, and photocatalytic degradation of methylene blue (MB) dye using a synthesized composite. The stable PCF is confirmed and characterized by analytical techniques, namely, fourier transform infrared (FTIR) and X‐ray photoelectron (XPS) spectroscopy, X‐ray diffraction (XRD), energy‐dispersive X‐ray (EDX), scanning electron microscopy (SEM), and vibrating sample magnetometry (VSM) analysis. The synthesized PCF nanocomposites are significantly crystalline in nature, having magnetic saturation of 10.47 emu g−1, and monoclinic crystalline structure as well as the size of nanocomposite is 39.54 nm verified by XRD pattern. SEM analysis revealed a regular porous and rough surface of nanocomposite. In addition, the nanocomposite divulged the remarkable efficient elimination of MB dye with maximum removal of 96% with good fitting of Langmuir isotherm, indication of monolayer formation on the catalyst surface through the interaction between nanocomposite and dye molecule. The adsorption kinetics bolstered the pseudo‐second‐order kinetic model, suggesting the adsorption process proceeded by chemisorption. The most notable feature of the nanocomposite is the reusability and good stability after several cycles, maintaining 90% after five cycles.